Polemik Gaji Dosen dalam Perspektif Literatur Tafsir Nusantara Klasik dan Kontemporer - Rosidin (STAI Ma'had Aly Al-Hikam Malang, 2024)
The hashtag #janganjadidosen is trending on various social media platforms due to the lack of financial welfare of lecturers. Empirical evidence is that 76% of lecturers take side jobs, so that the campus climate changes from an academic climate to an entrepreneurial climate. Until now, people have still been polemicising about lecturers' salaries. This polemic is rooted in different views on the lecturer profession. Is the lecturer profession a service that is classified as a non-commercial contract (tabarru’at), or is it a job that is classified as a commercial contract (mu’awadat)? This article is compiled using the thematic tafsir method (maudu'i) initiated by Abdul Hayy al-Farmawi with five national tafsir literature as primary sources, namely Tarjuman al-Mustafid by Abdurrauf al-Singkili; Marah Labid by Syaikh Nawawi; al-Ibriz by KH. Bisri Mustofa; Tafsir Al-Azhar by Buya Hamka and Tafsir Al-Mishbah by Quraish Shihab. There are four research results. First, the relevant keyword to discuss the polemics over lecturers’ salaries is the word “ajrun” and its derivations, mentioned 108 times in 99 verses. Second, the object of research is 10 verses that are directly related to the theme of lecturers’ salaries, namely Surat al-A'raf [7]: 113, Yunus [10]: 72, Hud [11]: 51, al-Kahf [18]: 77, al-Furqan [25]: 57, al-Shu’ara’ [26]: 109, al-Qasas [28]: 26, Yasin [36]: 21, Sad [38]: 86 and al-Shura [42]: 23. Third, based on the analysis of comparative interpretation (muqarin), the word ajrun and its derivatives in the Qur’an have three connotations of meaning: a) The meaning of non-commercial reward; b) The meaning of commercial wages; c) The meaning of “maslahat” which includes commercial and non-commercial benefits. Fourth, the meaning of maslahat is a parameter that is relevant to lecturer salaries in Indonesia today. Meanwhile, the scope of the meaning of maslahat can be elaborated by future research that uses the Burhani (empirical) or Irfani (idealistic) approach, as a complement to this article that uses the Bayani (textualist) approach. Tagar #janganjadidosen trending di berbagai media sosial, akibat minimnya kesejahteraan finansial dosen. Bukti empirisnya, 76% dosen mengambil kerja sampingan, sehingga iklim kampus berubah dari iklim akademik menjadi iklim wirausaha. Hingga saat ini, masyarakat masih berpolemik mengenai gaji dosen. Polemik ini berakar pada perbedaan pandangan dalam menyikapi profesi dosen. Apakah profesi dosen merupakan pengabdian yang tergolong akad tabarru’at yang bersifat non-komersil, atau merupakan pekerjaan yang tergolong akad mu’awadhat yang bersifat komersil. Artikel ini disusun dengan menggunakan metode tafsir tematik (maudhu’i) yang digagas oleh Abdul Hayy al-Farmawi dengan lima literatur tafsir nusantara sebagai sumber primer, yaitu Tarjuman al-Mustafid karya Abdurrauf al-Singkili; Marah Labid karya Syaikh Nawawi; al-Ibriz karya KH. Bisri Mustofa; Tafsir Al-Azhar karya Buya Hamka dan Tafsir Al-Mishbah karya Quraish Shihab. Ada empat hasil penelitian. Pertama, kata kunci yang relevan untuk membahas polemik gaji dosen adalah kata ajrun dan derivasinya yang disebutkan sebanyak 108 kali dalam 99 ayat. Kedua, objek penelitian adalah 10 ayat yang berkaitan langsung dengan tema gaji dosen, yaitu Surat al-A’raf [7]: 113, Yunus [10]: 72, Hud [11]: 51, al-Kahfi [18]: 77, al-Furqan [25]: 57, al-Syu’ara’ [26]: 109, al-Qashash [28]: 26, Yasin [36]: 21, Shad [38]: 86 dan al-Syura [42]: 23. Ketiga, berdasarkan analisis tafsir komparatif (muqarin), kata ajrun dan derivasinya dalam Al-Qur’an memiliki tiga konotasi makna: a) Makna pahala ukhrawi yang bersifat non-komersil; b) Makna upah duniawi yang bersifat komersil; c) Makna maslahat yang mencakup manfaat duniawi (komersil) dan ukhrawi (non-komersil). Keempat, makna maslahat merupakan parameter yang relevan dengan gaji dosen di Indonesia saat ini. Sedangkan ruang lingkup makna maslahat, dapat dielaborasi oleh penelitian berikutnya yang menggunakan pendekatan Burhani (empiris) maupun Irfani (idealis), sebagai pelengkap dari artikel ini yang menggunakan pendekatan Bayani (tekstualis). Kata Kunci: Dosen, Gaji Dosen, Tafsir Al-Qur’an, Tafsir Nusantara.